Criminal Aggravation for Perpetrators of Sexual Violence Crimes - aprianto nusa; Umar P; Vicky Ibrahim; Yetti S Hasan (Warmadewa Press, 2024)
The policy of aggravating perpetrators is to show the state's firm stance towards committing crimes of sexual violence. In reality, various punishments for sexual violence are not in line with the objectives of sexual punishment which regulate serious criminal sanctions for perpetrators of sexual violence. The perpetrator benefits from a decision that does not have a deterrent effect. The judge's consideration of imposing a sentence by taking into account the victim's role in the crime (precipitation victim) provides an opportunity for the judge to reduce the sentence of the perpetrator even though the concept of victim precipitation should be interpreted as a crime mitigation mechanism to minimize the risk of victimization. Therefore, this research aims to provide an overview of the criminal aggravation regulations, both those regulated in the Special Law on Sexual Violence and the new Criminal Code, as well as repositioning the meaning of victimization so that it does not become the basis for reducing criminal acts for perpetrators of sexual violence crimes. This research uses a socio-legal research approach with literature study techniques and in-depth interviews. The results of this research show that the concept of criminal enforcement regulated in Law No. 12/2022 concerning Crimes of Sexual Violence contains the threat of serious criminal and criminal aggravation, however this provision does not regulate the pattern of special minimum criminal threats (minima straf) while in Law No. 1 /2023 concerning the Criminal Code as a lex generalis regulates the concept of criminal punishment which can be considered as criminal aggravation, for example deelneming, concursus, and recidive